User-Involvement in the Development of a Culturally Sensitive Intervention in the Safe Pregnancy Study to Prevent Intimate Partner Violence - Flaathen, Eva Marie (Violence against women, 2021)
Intimate partner violence (IPV) during pregnancy has negative health impacts on the woman and the fetus. There is a lack of evidence supporting effective interventions to prevent IPV during pregnancy. This user-involvement study was conducted to get feedback on a culturally sensitive, tablet intervention containing questions about violence and safety-behaviors and a video promoting safety behaviors. This resulted in important feedback on the intervention content. Our findings show that women are in favor of disclosing IPV via a tablet. They suggested ways to address barriers for disclosure, such as safeguarding anonymity and creating a trustful relationship with the midwife.